Application of a perioperative nursing strategy in the surgical treatment of elderly patients: a narrative review† - Lyu Ding-Yang; Shuang Wei-Bing (Sciendo, 2022)
With the steady increase of older people in society, a progressively greater number of patients belonging to the geriatric group need surgical treatment. Since elderly patients with reduced physiological reserve and organ failure often have chronic diseases, geriatric syndrome, and other clinical problems, the perioperative nursing of elderly patients is more complicated. Therefore, we need to comprehensively consider clinical issues, such as patients' preoperative status, surgical risks, and postoperative quality of life and life expectancy, and conduct comprehensive evaluations and holistic, individualized, and continuous nursing and therapy through the participation of interdisciplinary teams to achieve better curative effects. Here, the perioperative nursing of elderly patients is reviewed, including preoperative evaluation and nursing, intraoperative management, and postoperative nursing.